Prolonged elevation of D‐dimer levels in convalescent COVID‐19 patients is independent of the acute phase response. (8th March 2021) - Townsend, Liam; Fogarty, Helen; Dyer, Adam; Martin‐Loeches, Ignacio; Bannan, Ciaran; Nadarajan, Parthiban; Bergin, Colm; O'Farrelly, Cliona; Conlon, Niall; Bourke, Nollaig M.; Ward, Soracha E.; Byrne, Mary; et al.
Abstract: Background: Persistent fatigue, breathlessness, and reduced exercise tolerance have been reported following acute COVID‐19 infection. Although immuno‐thrombosis has been implicated in acute COVID‐19 pathogenesis, the biological mechanisms underpinning long COVID remain unknown. We hypothesized that pulmonary microvascular immuno‐thrombosis may be important in this context. Methods: One hundred fifty COVID‐19 patients were reviewed at St James's Hospital Dublin between May and September 2020 at a median of 80.5 (range 44–155) days after initial diagnosis. These included patients hospitalized during initial illness ( n = 69) and others managed entirely as out‐patients ( n = 81). Clinical examination, chest x‐ray, and 6‐min walk tests were performed. In addition, a range of coagulation and inflammatory markers were assessed. Results: Increased D‐dimer levels (>500 ng/ml) were observed in 25.3% patients up to 4 months post‐SARS‐CoV‐2 infection. On univariate analysis, elevated convalescent D‐dimers were more common in COVID‐19 patients who had required hospital admission and in patients aged more than 50 years ( p < .001). Interestingly, we observed that 29% ( n = 11) of patients with elevated convalescent D‐dimers had been managed exclusively as out‐patients during their illness. In contrast, other coagulation (prothrombin time, activated partial thromboplastin time, fibrinogen, platelet count) and inflammation (C‐reactive protein, interleukin‐6, and sCD25) markers had returned to normal in >90% of convalescent patients. Conclusions: Elucidating the biological mechanisms responsible for sustained D‐dimer increases may be of relevance in long COVID pathogenesis and has implications for clinical management of these patients.